Методы энергосбережения в теплоснабжении Украины - Осипова, С. К. (НТУ "ХПИ", 2011)
Эта статья рассматривает вопросы внедрения энергосберегающих средств в теплоснабжении Украины. Представлено несколько видов классификаций энергосберегающих методов. Показаны проблемы внедрения энергосберегающих средств в Украине.

The article high light questions of introducing energy-saving technology in heat supply of Ukraine. Types of classification of methods of energy-saving are presented. Problems of introducing energy-saving means are regarded. Conclusions on this problems are given.
Keywords: экономическая политика государства; энергоэффективность; энергоносители; директивы EPBD